Secondary hemophagocytic lymphohistiocytosis and severe liver injury induced by hepatic SARS-CoV-2 infection unmasking Wilson's disease: Balancing immunosuppression. (February 2021) - Lubnow, Matthias; Schmidt, Barbara; Fleck, Martin; Salzberger, Bernd; Müller, Thomas; Peschel, Georg; Schneckenpointner, Roland; Lange, Tobias; Hitzenbichler, Florian; Kieninger, Martin; Lunz, Dirk; Graf, Bernhard; et al.
Highlights: We present an unusual case of a young COVID-19 patient presenting with hyperinflammation and severe liver injury. The underlying causative events were sHLH, hepatic SARS-CoV-2 infection induced by immunosuppression and Wilson's disease. SARS-CoV-2 was detected in hepatocytes by EM as well as virus isolation from a diagnostic liver biopsy. When immunosuppression is applied, (systemic) virus replication has to be closely monitored. Abstract: A 21-year-old woman was hospitalized due to coronavirus disease 2019 (COVID-19)-associated respiratory and hepatic impairment concomitant with severe hemolytic anemia. Upon diagnosis of secondary hemophagocytic lymphohistiocytosis, immunosuppression with anakinra and steroids was started, leading to a hepatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and viremia. Subsequent liver biopsy revealed virus particles in hepatocytes by electron microscopy and SARS-CoV-2 virus could be isolated and cultured. Immunosuppression was stopped and convalescent donor plasma given. In the differential diagnosis, an acute crisis of Wilson's disease was raised by laboratory and genetic testing. This case highlights the complexity of balancing immunosuppression to control hyperinflammation versus systemic SARS-CoV-2 dissemination.